The Application of Group Investigation Based on Hands on Activities to Improve Learning Outcomes Based on Higher Order Thinking Skills of Students at SMA Negeri 2 Pematangsiantar - Rosmaulina Adelina Ambarita; Yunastiti Yunastiti; Mintasih Indriayu (BIRCU, 2019)
The 2013 curriculum currently implemented in Indonesia is one of government attention to the educational world. One of the objectives of the curriculum implementation is the application of learning that is able to improve students' thinking skills which is generally called as higher order thinking skills (HOTS). However, conventional learning that is commonly implemented in Indonesia has not been able to meet the educational objectives. To solve these problems, a relevant learning model is required to improve students learning outcomes based on higher order thinking skills (HOTS). One of the appropriate learning models to solve this issue is the hands on activities investigation group learning model. This model is a learning model with a learning concept in which students are required to play a very active role in building their own knowledge through experiences encountered in groups that will be able to improve student learning outcomes based on higher order thinking skills. This article aimed to explain the ability of group investigation learning model based on hands activities in improving students learning outcomes based on higher order thinking skills. This research was quantitative research with experimental methods. The sample of this study was class X pis student of SMA Negeri 2 Pematangsiantar. The results showed that group investigation learning model based on hands on activities was able to improve learning outcomes based on higher order thinking skills of students at SMA Negeri 2 Pematangsiantar.